Augmented Reality Learning Media with a Problem-Based Learning Model to Enhance the Students' Comprehension on Mathematical Concepts - Priambudi, Dian; Sutopo, Yeri; Supriyadi (International Journal of Research in Education, 2024)
The aim of this research is to develop augmented reality learning media with a problem-based learning model and analyze the feasibility, practicality, and effectiveness of augmented reality learning media with a problem-based learning model in improving students' understanding of mathematical concepts. This research uses the research and development method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The sampling technique used is a random assignment, namely random sampling, where the experimental and control groups are chosen randomly from a lottery. The first lottery that came out was used as the experimental class, and the second lottery was used as the control class. Data collection techniques in this research used interview techniques, questionnaires, and tests. The results show (1) augmented reality learning media with a problem-based learning model is suitable for use, (2) augmented reality learning media is very practical to use, (3) understanding of mathematical concepts of students who receive learning with augmented reality media is better than students with conventional learning, and there are significant differences. (4) The augmented reality-based learning media developed is effective in use. The findings imply that the augmented reality learning media with a problem-based learning model can be an alternative and innovative media in assisting the student’s comprehension on mathematical concepts